Repertório social de crianças sob acolhimento institucional e habilidades sociais educativas de seus cuidadores - Guerra, Lívia Lira de Lima (2017)
A good social skills (SS) repertoire has been identified as a protective factor for problems in the course of child development, especially for children in vulnerable situations, as is the case of institutionalized children. The literature suggests that these children have marked deficits in their physical and cognitive development, compared to children with typical development. As such, one can question whether there are deficits in the socioemotional development of this specific population in terms of social skills and behavior problems. Given that a caregiver is the reference adult for these children, one may also question whether and how well this person promotes the child’s social skills development. The objective of this study was to characterize the social skills repertoire and behavior problems among children in residential care in four institutions located in three medium-sized cities in the interior of São Paulo - SP. It intended to also characterize the repertoire of Social Skills and Educative Social Skills (ESS) caregivers / guardians of these children, as well as investigate possible links between the repertoire of the caregivers and the children. Therefore, we used: the brazilian version of the Social Skills Rating System (SSRS); the Social Skills Inventory (IHS-Del-Prette); The Inventory of Educative Social Skills (IHSE-Parents version for caregivers). Participants were 36 children, of both genders, aged 6 to 12 years and 19 caregivers between 23 and 62 years years of age. The descriptive and inferential statistical analyses showed that: (1) the sample of children had scores below norms in social skills, especially for empathy, with externalizing behavior problems, according to the caregivers, were of above average frequency; (2) caregivers had scores classified as medium repertoire (lower and upper) in social skills and below average in educative social skills; (3) children with higher social skills showed fewer behavior problems; (4) .Children with a higher SS repertoire tended to more positively assess the caregivers’s social educative skills repertoire. (5) No significant result was found among the children's caregivers' and SS's repertoire of Educative Social Skills, as is expected in the case of parents and children; (6) However, in the case of the sample of caregivers from the present study, attention and affection / talk / dialogue skills were the most deficient, precisely those positively correlated with the children's social skills repertoire and present in the repertoire of parents whose children have a broader repertoire of SS. It was hypothesized that possibly caregivers invest more in those children with better repertoire. We discuss, therefore, differences in institutional and family contexts and the importance of caregivers as models of secure attachment and expression of affection towards the child. Such findings can also be considered in the hiring of professional caregivers as well as in the planning of interventions based on ESS. The data also suggest the relevance of interventions aimed at promoting SS of institutionalized children as a way of contributing to their social-emotional development.